Selected Problems in Physical Chemistry Strategies and Interpretations - Ilich, Predrag-Peter.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This book is a collection of 50 original problems in physical chemistry including several living systems. Each problem is accompanied by a detailed step-by-step solution, organized as strategy, assumptions, approximations, numerical calculation and interpretation. Solutions to the key problems (e.g. thermal equilibration, ligand-receptor interaction, aminoacid zwitterions, HOMO-LUMO gap) are accompanied by simple introductory explanations. In addition, informal notes are provided on difficult concepts, for example: entropy, reaction activation barrier, wave mechanics. Schemes, diagrams and structural formulas accompany most solutions and explanations. Thus, this textbook may serve as a self-tutorial for undergraduate students in physical chemistry, biophysics, biochemistry, and medicinal chemistry.
Mechanics -- Mechanical Work -- Mechanics of Gases -- Basic Thermodynamics -- Heat Transfer -- Thermodynamics -- Mixtures and Chemical Thermodynamics -- Mixtures and Solutions -- Chemical Reactions and Gibbs Free Energy -- Gibbs Free Energy and Chemical Equilibria -- Ionic Properties and Electrochemistry -- Ions -- Electrochemistry -- Kinetics -- Kinetics -- Structure of Matter: Molecular Spectroscopy -- The Structure of Matter -- Interaction of Light and Matter.
Keywords: Chemistry; Chemistry, Physical organic; Biochemistry; Chemistry; Physical Chemistry; Biophysics and Biological Physics; Biochemistry, general; Medicinal Chemistry